Acoustics in buildings - Grehant, Bernard (Thomas Telford, 1996)
This work explains, in a practical way, the fundamental principles needed for understanding noise, its cause and the means of dealing with it. It presents a strategy for optimising a building's internal environment in terms of noise and its associated problems, addressing all stages of the process from the motor design to installation.